2006
DOI: 10.1021/ac052152o
|View full text |Cite
|
Sign up to set email alerts
|

Wide Electrochemical Window at the Interface between Water and a Hydrophobic Room-Temperature Ionic Liquid of Tetrakis[3,5-bis(Trifluoromethyl)phenyl]borate

Abstract: Ionic liquids composed of a hydrophobic anion, tetrakis[3,5-bis(trifluoromethyl)phenyl]borate (TFPB-), and various aromatic and aliphatic ammonium have been prepared. TFPB salts of N-octadecylisoquinolinium (C18Iq+) and trioctylmethylammonium (TOMA+) show low melting points of 31 and 36 degrees C, respectively, whereas TFPB-based ionic liquids of 1-alkyl-3-methylimidazolium with the alkyl chain length of 5-12 show melting points lower than 90 degrees C. The [C(18)Iq][TFPB]|water (W) and [TOMA][TFPB]|W interfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
102
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(105 citation statements)
references
References 30 publications
1
102
1
Order By: Relevance
“…We also found similar voltammograms of ion transfer at a micro liquid-liquid interface formed at the tip of a glass capillary when the capillary containing an aqueous solution was dipped in a hydrophobic RTIL, N-octadecylisoquinolinium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate. 27 The scan-rate independent plateau suggests that the shape of the capillary shank close to the orifice is not cylindrical. From numerical calculations of voltammograms, we have recently confirmed that such a steady-state current is reproduced when the tip geometry is noncylindrical, that is, conical or tapered.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We also found similar voltammograms of ion transfer at a micro liquid-liquid interface formed at the tip of a glass capillary when the capillary containing an aqueous solution was dipped in a hydrophobic RTIL, N-octadecylisoquinolinium tetrakis[3,5-bis(trifluoromethyl)phenyl]borate. 27 The scan-rate independent plateau suggests that the shape of the capillary shank close to the orifice is not cylindrical. From numerical calculations of voltammograms, we have recently confirmed that such a steady-state current is reproduced when the tip geometry is noncylindrical, that is, conical or tapered.…”
Section: Resultsmentioning
confidence: 99%
“…However, hydrophobic RTILs are generally much more viscous than conventional solvents; the viscosity is typically two orders of magnitude greater than that of water. [21][22][23][24][25][26][27] A large solution resistance in the RTIL phase makes it diffcult to obtain voltammograms without distortion, even after applying positive-feedback compensation of the solution resistance. 17,19 For voltammetry in highly resistive media, ultramicroelectrodes are known to be useful.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the group of Kakiuchi has been very active [6][7][8] since their pioneering work in 2003 [9], and the first review paper on this topic was published recently [10]. Ion transfer at the W|RTIL interface is a special case of ion transfer at the interface between two immiscible electrolyte solutions (ITIES), which enables the study and detection of ions not easily oxidisable or reducible at solid|liquid interfaces.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we report the behaviour of a W|RTIL micro-interface array formed between water and the RTIL trihexyltetradodecylphosphonium tris(pentafluoroethyl)trifluoromethylphosphate ([P 14,6,6,6 ][FAP]) within a silicon micropore membrane (consisting of 30 micropores of ca. 23 µm diameter).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, ILs are termed "designable solvents" [8], and various applications have reported for them. In analytical chemistry, ILs were used as stationary phases in gas chromatography [9][10][11], additives for capillary electrophoresis [12][13][14][15], matrices for MALDI [16][17][18], as well as solvents for spectral analysis [19][20][21] and electrochemistry [22]. Several reviews that focus on these topics have been published recently [23][24][25][26][27].…”
Section: Introductionmentioning
confidence: 99%